Processing of Milkfish and Moringa Flour as Alternative Superfoods for Handling Stunting in Bone Regency - Musni, Musni; Malka, St.; Syam, Azniah (Journal La Medihealtico, 2024)
Stunting has a big influence on children's growth and development, both motoric and verbal development. Stunting can be prevented by fulfilling quality energy intake. Modification of additional food for toddlers by using local food through a touch of technology is the strategy offered in this research. This study aims to evaluate the effect of fortification of Moringa leaf flour in milkfish crackers on organoleptic characteristics, including color, aroma, texture and taste. The cracker samples were fortified with Moringa leaf flour at concentrations of 0%, 2.5%, 5% and 7.5%. The assessment is carried out by panelists who provide scores for each parameter. The results showed that fortification up to 2.5% did not affect color and aroma, and improved texture, but reduced taste acceptability. Fortification at levels of 5% and 7.5% reduced the acceptability of taste and color although the texture remained good.